Alcohol Screening and Brief Intervention in Primary Health Care in Kazakhstan-Results of a Cluster Randomised Pilot Study - Uwe Verthein; Harald Lahusen; Marcus Sebastian Martens; Mariya Prilutskaya; Oleg Yussopov; Zhanar Kaliyeva; Bernd Schulte (Frontiers Media S.A., 2022)
Objective: The aim of this pilot trial was to assess the feasibility of ASBI in primary health care units (PHCUs) in Kazakhstan.Methods: A two-arm cluster randomised trial in five PHCUs based on the RE-AIM framework for implementation studies was carried out. Patients with AUDIT-C scores ≥4 for females and ≥5 for males received a brief face-to-face intervention delivered by a trained physician plus information leaflet (intervention group, IG) or simple feedback including a leaflet (control group, CG).Results: Among 7327 patients eligible for alcohol screening according to the inclusion criteria 1148 patients were screened (15.7%, IG: 11.5%, CG: 27.3%). 12.3% (N = 141) were tested AUDIT-C positive (IG: 9.9%, CG: 15.1%). Out of 112 physicians invited, 48 took part in the ASBI training, 31 finally participated in the study, 21 in the IG (2 PHCUs), 10 in the CG (3 PHCUs). The majority of physicians did not have difficulties in performing the intervention.Conclusion: ASBI is feasible and can be implemented into PHC settings in Kazakhstan. However, the implementation depends on the willingness and interest of the PHCU and the physicians.